The production of bio-jet fuel from Botryococcus braunii liquid over a Ru/CeO2 catalyst. Issue 102 (20th October 2016) - Zhang, Kun; Zhang, Xu; Tan, Tianwei
Abstract : In this study, the conversion from Botryococcus braunii liquid to bio-jet fuel via a Ru/CeO2 catalyst was conducted. Abstract : In this study, the conversion from Botryococcus braunii liquid to bio-jet fuel via a Ru/CeO2 catalyst was conducted. At first, novel Ru/CeO2 catalysts were prepared in order to increase the catalytic activity. "Ru/CeO2 -alcohol thermal" showed the highest activity: the squalane conversion exceeded 90%, an increase of about 22% in comparison with "Ru/CeO2 -impregnation". When the B. braunii liquid was used as the raw material, no obvious catalytic activity was noticed. Therefore, the influence of impurities in the B. braunii liquid on the Ru/CeO2 reaction were preliminarily analysed, confirming that the pigments (such as β-carotenoid) and the oxygen compounds (such as fatty acids) were the main factors influencing the Ru/CeO2 reaction. Based on these results, the reaction process was optimized: prolonging the reaction time and pretreating the B. braunii liquid with H2 . Finally, the production of bio-jet fuel over Ru/CeO2 was successfully achieved.